(3Jbhje aGYdjI HQGeL GdJhYjI Ydi GdHjFI aj cJGH GdJQHjI ddUa GdNGeS GdCSGSj aj eOGQS Ebdje GdNQhH GdQSejIs - (3GdMGL, aGOjGs ((3HjQhJs (3LGeYI GdbOjS jhSas, 2006)
(3LGAJ ETcGdjI GdOQGSI GdMGdjI aj eYQaI eOi bOQI HQGeL GdJhYjI Ydi GdHjFI Ydi EjUGd GdQSGdI GdHjFjI GdeQLhI ddJdGejP, hPdc ef NdGd eYQaI eOi bOQI cJGH GdJQHjI ddUa GdNGeS GdCSGSj aj eOGQS Ebdje GdNQhH GdQSejI Ydi fTQ GdhYj GdHjFj hYdi Ndb GJLGgGJ EjLGHjI JLGg GdHjFI dOi GdJdGejP(B. (3ef gfG gOaJ GdOQGSI deYQaI (B1) (3eOi bOQI GdcJGH Ydi ZQS GdeYQaI GdHjFjI dOi GdJdGejP, hYdi JMQjc GdTYhQ GdhWfj hNdb MS GdeSDhdjI GdHjFjI dOjge(B. 2) (3eOi bOQI GdchGOQ GdJYdjejI Ydi EjUGd GdQSGdI GdHjFjI GdeWdhHI YHQ gPG GdcJGH, heOi GYJeGOgG Ydi GdfTGWGJ GddGUajI(B. 3) (3eSJhi GdhYj GdHjFj GdPj jJeJY Hg Cgd GdJdGejP, heG JCKjQ Pdc Ydi GdCgOGa GdHjFjI GdeQGO JMbjbgG ef NdGd GdcJGH(B. (3EYJeOJ GdOQGSI GdefgL GdJagej, MjK GfMUQJ aj Ebdje GdNQhH haj GdUa GdNGeS GdCSGSj aj eOGQSgG GdQSejI, hGfbSeJ GdYjfI Edi KdGKI CbSGe(B: (3GdJdGejP; (B121 (3JdejkPG JhRYhG (B74 (3PchkQG h(B47 (3EfGkKG, hGdCSGJPI hGdCgd(B. (3YQVJ Ydjge (B3 (3COhGJ hgj(B: (3QGFR hqLg Edi GdJdGejP, hGSJeGQJGf ddCSGJPI hGdCgd(B. (3hNdUJ GdOQGSI Edi eG jdj(B: 1) (3Ef OQLGJ GdeYQaI GdHjFjI GdJj Jecf GdJdGejP ef GdMUhd YdjgG ef NdGd cJGH GdJQHjI JQGhMJ Hjf eJhSWI hSjFI, hCf eJZjQ GdLfS hGdehbY de jcf dgeG Cj JCKjQ Ydi Pdc(B. 2) (3Ef fSHI eQJaYI ef GdCSGJPI GaJbQJ Edi GdNHQGJ GdHjFjI GdJj JDefgG dgG GdOhQGJ GdJOQjHjI, hCXgQJ EbJfGYkG HGdfTGWGJ GddGUajI, aj Mjf Cf eJZjQ GdLfS de jXgQ Cj aQhbGJ OGdI(B. 3) (3Ef GdfSHI GdCYdi ef GdCgd JOQc NWhQI GdhVY GdHjFj heOi JgOjOg deSJbHdge hMjGJge, hJYj VQhQI GdeTGQcI aj GdMd, EdG Cfge ZjQ eSJYOjf ddbjGe HGdNWhGJ GdVQhQjI hGdUMjMI hdJbOje GdJfGRd aj SHjd MjGI CcKQ UMI hWeCfjfI, gPG hde JXgQ Cj aQhbGJ OGdI ajeG jNU eJZjQ GdLfS heJZjQ GdefWbI(B. 4) (3Ef GdeLJeY HCcedg HMGLI edMI Edi GdJQHjI GdHjFjI GdJj JYJHQ GdSHjd GdChMO hGdCaYd ddNdGU ef GdeTcdI GdHjFjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdJQHjI GdHjFjIs; Education pour l$1 (Benvironnements; Environmental education; Iklim el Kharoub; Iklim el Kharoub; Public Sector Elementary Education Civic Education Textbooks; Secteur Public Cycle primaire Education Civique Livres Scolaires; (3Gbdje GdNQhHs; (3GdJYdje GdQSej GdeQMdI GdGHJOGFjI JYdje GdJQHjI GdhWfjI hGdJfTFI GdeOfjI GdcJGH GdeOQSjs